The Impact of Artificial Intelligence on the Criminal Justice System: Ethical and Legal Challenges - Flora, Henny Saida; Xu, Shanshan; Xavier, Murphy; Cale, Woolnough; Syahputra, M. (Rechtsnormen: Journal of Law, 2024)
Background: Artificial Intelligence (AI) is increasingly being integrated into the criminal justice system, promising to enhance efficiency, accuracy, and decision-making. However, the use of AI also raises significant ethical and legal challenges, including concerns about bias, fairness, transparency, and accountability. These challenges necessitate a thorough examination of AI's impact on the criminal justice system to ensure its benefits are realized without compromising ethical and legal standards. Objective: This study aims to evaluate the impact of AI on the criminal justice system, focusing on the ethical and legal challenges it presents. The research seeks to understand how AI technologies are being implemented, their effects on decision-making processes, and the extent to which they adhere to ethical and legal principles. The goal is to identify best practices and propose solutions to mitigate potential risks. Methods: A mixed-methods approach was employed, combining quantitative surveys and qualitative interviews. Quantitative data were collected from 250 criminal justice professionals, measuring their perceptions of AI's impact on various aspects of the justice system. Qualitative interviews with 40 key stakeholders provided deeper insights into the ethical and legal challenges associated with AI integration. Data were analyzed using statistical methods for the surveys and thematic analysis for the interviews. Results: Findings indicate that AI can significantly enhance the efficiency and accuracy of the criminal justice system but also presents substantial ethical and legal challenges. Issues such as algorithmic bias, lack of transparency, and accountability were frequently highlighted. Best practices identified include implementing rigorous validation processes, ensuring transparency in AI decision-making, and establishing clear accountability frameworks. Conclusion: While AI holds significant promise for improving the criminal justice system, addressing ethical and legal challenges is crucial for its successful integration. Implementing best practices can mitigate risks and ensure that AI technologies are used responsibly. Future research should focus on developing comprehensive guidelines and policies to govern the use of AI in the criminal justice system.